2009
DOI: 10.1016/j.joen.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Microsurgery: An In Vivo Evaluation of Endodontic Root-End Filling Materials

Abstract: The purpose of this study was to assess the healing of periapical tissues using three different materials (IRM [L.D. Caulk Inc, Dentsply International Inc, Milford, DE], Geristore [Den-Mat, Santa Maria, CA], and MTA [ProRoot MTA; Dentsply Tulsa Dental Specialties, Tulsa, OK]) after endodontic microsurgery in an animal model. Using beagle dogs as a study model, 48 bicuspids were accessed, instrumented, and intentionally infected. The surgical procedures were performed after 30 days following the radiographic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
2
34
2
Order By: Relevance
“…Geristore showed the least favorable healing in the histologic evaluation; no statistical difference was noted between MTA and IRM (38).…”
Section: Root-end Fillingmentioning
confidence: 75%
See 1 more Smart Citation
“…Geristore showed the least favorable healing in the histologic evaluation; no statistical difference was noted between MTA and IRM (38).…”
Section: Root-end Fillingmentioning
confidence: 75%
“…Many investigations have compared MTA as a root-end filling material with other currently used materials (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Several investigations concerned infected root canals and induced periapical lesions before filling root-end preparations with MTA (29,(33)(34)(35)37), whereas in others, periapical surgeries were performed after root canal therapy in sound, intact teeth (28,30,32).…”
Section: Root-end Fillingmentioning
confidence: 99%
“…Positive histologic and radiographic outcomes showed that MTA was suitable root-end filling material for periradicular surgery, providing appropriate healing response from periapical tissues (3). MTA has been shown to be bioactive because of its ability to promote a biomineralization process (4).…”
mentioning
confidence: 99%
“…Numerous materials have been recommended for rootend obturation, and many studies have attempted to identify an ideal material; however, an ideal material has not been found. [7] The most commonly used materials are mineral trioxide aggregate (MTA) and IRM. [7] Recent studies show that although IRM achieved the most favorable healing response, both radiographically and histologically, these results were not statistically different from MTA.…”
Section: Discussionmentioning
confidence: 99%